The Use of Non-Prescribed Medicines in Infants from Birth to Six Months in Rural Areas of Polokwane Municipality-Limpopo Province, South Africa - Maishataba Solomon Makwela; Eric Maimela; Makoma Melicca Bopape; Reneilwe Given Mashaba (MDPI AG, 2024)
The WHO and UNICEF recommend that only breastmilk, vitamin drops, oral rehydration solution, and prescribed medicine can go through the infant's mouth. Non-prescribed medications (NPM) include over-the-counter medications and traditional medicine and are contraindicated during infancy. Furthermore, the updated exclusive breastfeeding (EBF) indicator details that herbal fluids and similar traditional medicines are counted as fluids, and infants who consume these are not exclusively breastfed. However, the use of these items is common among caregivers for various reasons, including religious reasons, cultural beliefs, prevention of diseases, and the treatment of diseases. The practice of administering NPM before six months of age undermines exclusive breastfeeding and can result in undesirable health outcomes. Methods: The purpose of this study was to determine the prevalence of NPM, describe the types of medications used, and explain why caregivers use NMP in infants younger than six months of age. A quantitative approach and a facility-based cross-sectional survey were used to conduct this study. Convenience sampling was used to select clinics, and proportionality and simple random sampling were used to select 146 participants. Data were analyzed using SPSS (29). A p-value of p < 0.05 was considered significant. Results: In this study, the prevalence of NPM was 75.3%. Of the 146 participants, most were 25-35 years old (54%) and first-time mothers (36.3%). More caregivers had high school and matric (67.1%), and 84.2% of caregivers delivered in public health facilities. Almost three-quarters are unemployed (66.7%) and on a child support grant (56.4%). About 43.6% of infants received NPM within the first month of life. The main source of advice to give NPM was family members (86.4%). The main reasons for administering NPM were the treatment of the umbilical cord (57.3%) and the prevention of colic (32.7%). The results show a statistically significant association between the administration of medication and the age of the infant, p < 0.005. Conclusions: Non-prescribed medications are highly prevalent in the rural areas of Polokwane and are practiced by caregivers between the ages of 25-35 years advised by the families. Access to self-medication should be controlled, especially in the first month of life. Interventions to reduce the use of NPM should be targeted at young mothers and their families.